PENERAPAN PENDEKATAN SAINTIFIK DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VIII A DI SMP NEGERI 8 MALLAWA MAROS - Rahmawati, Dwi; Syahid, Akhmad; Aidil Sudarmono R, Muh; Mustamin; Raehana, Syarifa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This researcher aims to describe the application of scientific approaches and analyze how much improvement in learning outcomes in Islamic Religious Education class VIII.B learning at SMPN 8 Mallawa Maros. The purpose of this study is to find out the application of scientific approaches and evaluate the learning outcomes of students in Islamic religious education subjects in class VIII.B SMPN 8 Mallawa Maros. The type of research used is Classroom Action Research (PTK) which is carried out in two cycles. Each cycle consists of the stages of planning, implementation, observation, and reflection. The research subjects amounted to 30 students. The data collection techniques used are observation, tests, and documentation. The results of the research show that the application of scientific approaches can improve student learning outcomes. In the preliminary cycle, 9 students (30%) achieved learning completeness with an average score of 68.67. In the first cycle, it increased to 16 students (53.33%) with an average score of 75.67. In the second cycle, it increased to 27 students (90%) with an average score of 92.67. In addition, students become more active in participating in learning through observing, observing, collecting information, reasoning, and communicating.